Electrically charged topological solitons - Gomes, J. F.; Gueuvoghlanian, E. P.; Sotkov, G. M.; Zimerman, A. H. (Elsevier B.V., 2001)
Two new families of T-dual integrable models of dyonic type are constructed. They represent specific A(n)((1)) singular non-abelian affine Toda models having U(1) global symmetry. Their I-soliton spectrum contains both neutral and U(I)-charged topological solitons sharing the main properties of 4-dimensional Yang-Mills-Higgs monopoles and dyons. The semiclassical quantization of these solutions as well as the exact counterterms and the coupling constant renormalization are studied. (C) 2001 Elsevier B.V. B.V. All rights reserved.